Elucidating measures of systemic racism to mitigate racial disparities in kidney transplantation. Issue 5 (October 2021) - Wilson, Elena M.; Chen, Andy; Johnson, Morgan; Perkins, Jamilah A.; Purnell, Tanjala S.
Abstract : Purpose of review: Given recent national attention to the role of racism in perpetuating racial inequities in society and health, this review provides a timely and relevant summary of key measures of systemic racism in kidney transplantation. More specifically, the review identifies current and promising interventions, whereas highlighting the need for more sustainable and impactful interventions. Recent findings: Racial disparities persist in kidney transplantation. Black and Hispanic individuals are less likely to receive a kidney transplant than non-Hispanic Whites despite disproportionately higher rates of kidney failure. Studies demonstrate that socioeconomic factors do not fully explain existing racial disparities in transplantation. Systemic racism at all levels, individual, interpersonal, institutional, and structural, is at the core of racial disparities, and current interventions are insufficient in mitigating their effects. Thus, targeted and sustainable interventions must be implemented to mitigate systemic racism in kidney transplantation. Summary: Systemic racism in all its forms continues to influence disparities at all stages of kidney transplantation. This paper highlights recent findings that shed light on how racism contributes to racial disparities in kidney transplantation. Using these findings to identify targets and strategies for mitigation, relevant interventions and policies that show promise are detailed.